ENGLISH WRITING SKILLS THROUGH PERCEPTION OF SIRI’ CULTURAL VALUES: OPTIMISM, SOCIAL SUPPORT, AND ACADEMIC SELF-EFFICACY - Subhan Ajrin Sudirman; Achmad Nurmandi; Khoiruddin Bashori (Jurnal Cakrawala Pendidikan, 2020)
The mastery of foreign languages, in particular English which is applied predominantly in the international scope is one form of improving the quality of an indvidual. This research aims to find empirical support for relationships between optimism, social support, academic self-efficacy and mastery of academic English paragraph writing skills mediated by perceptions of Siri’ cultural values. Siri’ cultural values are living laws which becomes the guidance in think, act, and build interpersonal relationship with other individuals. The instruments of this research applied writing tasks, scales of optimism, social support, academic self-efficacy, and perceptions of Siri’ cultural values. Data were analyzed using structural equation modeling. The results show that the relationship between optimism, social support, and academic self-efficacy and mastery of academic English paragraph writing skills will be stronger when students are able to perceive cultural values of Siri’ well. It is worthy of attention for educators and education observers that when students are required to be able to master a learning material not only from the cognitive side concerned, but also the psychological side of students must be considered.